A compact fiber‐optic probe‐based singlet oxygen luminescence detection system. Issue 2 (25th July 2016) - Gemmell, Nathan R.; McCarthy, Aongus; Kim, Michele M.; Veilleux, Israel; Zhu, Timothy C.; Buller, Gerald S.; Wilson, Brian C.; Hadfield, Robert H.
Abstract : This paper presents a novel compact fiberoptic based singlet oxygen near‐infrared luminescence probe coupled to an InGaAs/InP single photon avalanche diode (SPAD) detector. Patterned time gating of the single‐photon detector is used to limit unwanted dark counts and eliminate the strong photosensitizer luminescence background. Singlet oxygen luminescence detection at 1270 nm is confirmed through spectral filtering and lifetime fitting for Rose Bengal in water, and Photofrin in methanol as model photosensitizers. The overall performance, measured by the signal‐to‐noise ratio, improves by a factor of 50 over a previous system that used a fiberoptic‐coupled superconducting nanowire single‐photon detector. The effect of adding light scattering to the photosensitizer is also examined as a first step towards applications in tissue in vivo . Abstract : This paper demonstrates an optical fiber‐based probe for singlet oxygen detection. Such a probe is capable of delivering pump illumination to the sample, while simultaneously monitoring the near infrared phosphorescence. Patterned gating with a peltier cooled detector results in an efficient, affordable, and practical detection system suitable for clinical Photodynamic Therapy studies.